Two imperfectly bonded half-planes with an arbitrary inclusion subject to linear eigenstrains in anti-plane shear (Archives of Mechanics - Test, 2019)
An analytic solution to the anti-plane problem of an arbitrary inclusion within an elastic bimaterial under the premise of linear eigenstrains is developed. The bonding along the bimaterial interface is considered to be homogeneously imperfect. The boundary value problem is reduced to a single nonhomogeneous first order differential equation for an analytic function prescribed in the lower half-plane where the inclusion is located. The general solution is given in terms of the imperfect interface parameter and an auxiliary function constructed from the conformal mapping function. In particular, the solution obtained for a circular inclusion demonstrates that the imperfect interface together with the prescribed linear eigenstrains have a pronounced effect on the induced stress field within the inclusion and show a strong non-uniform behaviour especially when the inclusion is near the imperfect interface. Specific solutions are derived in a closed form and verified with existing solutions.